Vengeance [videorecording (DVD)] - Novak, B. J., 1979-; Novak, B. J., 1979-; Holbrook, Boyd, 1981-; Smith-Cameron, J.; Tipton, Analeigh, 1988-; Kutcher, Ashton, 1978-; Rae, Issa; Amara, Isabella, 1998-; Cameron, Dove (Focus Features, 2022)
A journalist and podcaster from New York City attempts to solve the murder of a girl he hooked up with and travels down to Texas to investigate the circumstances of her death and discover what happened to her.